Assessing knowledge of Pediatric Diabetes Mellitus among Nurses at Turaif General Hospital, Saudi Arabia - Alruwaili, Ziyad Osailan; Alanzi, Waajid Awad; Alhazmi, Ayesh Hussein; Alrwaili, Mansur Mohammd (Journal of medical and pharmaceutical sciences, 2023)
This research aimed to explore the level of nurses’ knowledge of pediatric Diabetes Mellitus (DM) at Turaif General Hospital, Saudi Arabia, and the knowledge deficits among nurses about this serious medical concern. Also, the job and demographic characteristics of the nurses are studied in relation to their knowledge of pediatric DM. This research used the descriptive approach. The questionnaire is used in this study as the main data collection tool. The population of this research consists of all pediatric nurses at Turaif General Hospital in Saudi Arabia whose number is (220) nurses. The duration of the study took about (1) month starting from 01 October 2022 until 02 November 2022. The results of the study showed that the overall mean of the participant’s responses to items of the questionnaire is (3.04) which is a medium mean, indicating that the nurses have a moderate level of knowledge of diabetes mellitus in children. The nurses’ knowledge of pediatric DM in terms of occurrence, risk factors, and nutrition was moderate. On the other hand, it was shown that there are statistically significant differences between the mean scores of the participant’s responses to the items of the questionnaire due to the variable of years of experience and no difference due to job and educational level variables. The researchers recommended that special training further to essential nursing education will strengthen the knowledge and abilities of nurses.